Sarcopenia and Frailty in Cirrhotic Patients: Evaluation of Prevalence and Risk Factors in a Single-Centre Cohort Study - Kadri Atay; Seval Aydin; Billur Canbakan (Medicina)
Background and Objectives: Sarcopenia and frailty adversely affect morbidity and mortality in patients with liver cirrhosis. This study aimed to investigate the prevalence of sarcopenia and frailty in cirrhotic patients and to identify the contributing factors. Materials and Methods: This study was conducted in adult patients diagnosed with cirrhosis in a single-center cohort study who were under follow-up in the gastroenterology outpatient clinic. Patients were evaluated using the SARC-F questionnaire, FRAIL index, handgrip strength measurements, and various biochemical parameters. Results: Of the 100 patients included in the study, 58.7% were male, with a median age of 66.5 years. The prevalence of sarcopenia was 32%. Patients with sarcopenia had significantly lower body mass index (BMI) and higher model for end-stage liver disease (MELD)-Na and Child–Turcotte–Pugh (CTP) scores. According to the FRAIL scale, pre-frailty was highly prevalent among patients (60%). Significant negative correlations were observed between the SARC-F score and BMI, handgrip strength, albumin, vitamin D, and sodium levels. Conversely, significant positive correlations were identified between the SARC-F score and age, CTP score, MELD-Na score, bilirubin, AST, ALT, and ferritin levels. Conclusions: This study demonstrated a high prevalence of sarcopenia and frailty among cirrhotic patients. These findings warrants further investigation in longitudinal studies for hard clinical outcome and mortality.